ANALISIS YURIDIS PENGAMBILALIHAN SAHAM PT PRIMA TOP BOGA OLEH PT NIPPON INDOSARI CORPINDO, TBK DARI PERPEKTIF UNDANG-UNDANG NOMOR 5 TAHUN 1999 (Studi Kasus Putusan Komisi Pengawas Persaingan Usaha Nomor: 07/KPPU-M/2018) - Suradiyanto suradiyanto; Dinny Wirawan Pratiwie (Law Department, University of Widya Gama Mahakam Samarinda, 2019)
The purpose of this study is to review and analyze the legal consequences of acquisitions made on limited liability companies; and based on theconsiderations used by KPPU to determine that PT Nippon Indosari Corpindo, Tbk. Has violated Law Number 5 of 1999 .This research is normative legal research. Secondary data collection in library research is done by studying documents. The data analysis method used in this study is descriptive and analyzed qualitatively.The results of this study are: (1) Acquisition or Acquisition of Limited Liability Companies can also provide legal consequences affecting the Limited Liability Company. The legal consequences referred to in the Limited Liability Company are the legal consequences both institutionally, namely shareholders, employees, and third parties, as well as the legal consequences of certain parties, especially to third parties or creditors from the acquired limited liability company. In practice that has happened so far, the status of creditors' receivables in a limited liability company that has been acquired is the responsibility of the new Shareholders ; and (2) In the reading of the decision it was also explained that the reported party had acquired / taken over shares of PT Prima Top Boga on January 24, 2018, amounting to 32,051 shares (issuance of new shares) taken over by adding capital worth Rp31,499,722,800 , 00 (thirty one billion four hundred ninety nine million seven hundred twenty thousand eight hundred rupiahs) by Pt Nippon Indosari Corpindo, Tbk. After a long process, through the Merger Directorate, it was conveyed that based on the calculation of calendar days, notices of the takeover of shares of the PT Prima Top Boga company should be notified to the Commission no later than March 23, 2018. However, the reported report took place on March 29, 2018. In accordance with PP No. 57 of 2010 that the reported party is obliged to notify the Commission of the acquisition of shares no later than 30 (thirty) working calendar days from the date the juridically effective Business Entity, Business Entity Consolidation or Takeover of Company Shares are effective.